FRI0086 Fatigue in Patients with Rheumatoid Arthritis Selected for Biological Treatment in the Daily Clinic: Associations with Classical Measures of Disease Activity. (10th June 2014) - Egsmose, E.L.; Madsen, O.R.
Abstract : Background: The nature of the fatigue frequently experienced by patients with inflammatory joint diseases is not well understood (ref.). Objectives: The purpose of the present study was to examine associations between fatigue (FTG) and classical measures of disease activity in rheumatoid arthritis (RA) patients selected for initiation of biological treatment. Methods: Data on 221 RA patients planned to initiate treatment with a biological agent due to high and uncontrolled disease activity were extracted from the Danish registry for biological treatment in rheumatology (DANBIO). Simple linear correlation analyses (Pearson's r) were used to assess the relationship between FTG as assessed on a visual analogue scale (VAS) (range 0-100) and classical measures of disease activity [swollen and tender joints, CRP, VAS global assessment of physician (PhGl) and patient (PaGl), VAS pain, HAQ], and the composite score DAS28-CRP and age. The best predictors of FTG were identified using stepwise multiple regression analysis. 95% lower and upper limits of agreement (LLoA and ULoA) with VAS patient global and VAS pain and the corresponding biases were obtained from Bland-Altman analyses. Results: Mean age was 57±14 years, mean DAS28 5.0±0.9 and mean FTG 60.7±22.7. FTG was most strongly correlated with PaGl (r =0.83), pain (r =0.75) and HAQ (r =0.41) (all p<0.0001) and most weakly with CRP (r =0.04, NS) and PhGl (r =0.03, NS). The most important predictor of FTG was PaGl (beta =0.68, p<0.0001) followed by VAS pain (beta =0.18, p<0.05) (R 2 =0.70, p<0.0001). No other measures added significantly to the regression equation. Results were unchanged after leaving out DAS28-CRP. The bias [LLoA; ULoA] for FTG versus PaGl was -2.9±13.1 (p<0.001) [-28.6; 22.8] and for FTG versus VAS pain 2.3±16.1 (p<0.001) [-29.3; 33.6]. Conclusions: FTG was poorly explained by objective measures of disease activity. The most important predictors were PaGl and VAS pain but although these two measures were nearly identical with FTG on the group level, large intra-individual differences were observed. The findings emphasise the complexity of understanding and dealing with FTG in the daily RA clinic. References: Nikolaus S et al. Fatigue and factors related to fatigue in rheumatoid arthritis: a systematic review. Arthritis Care Res (Hoboken) 2013; 65: 1128-46. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2714